Un lugar incierto - Vargas, Fred (Nuevos tiempos (Madrid, Spain), 2012)
When Commissaire Adamsberg, the chief of police in Paris's 7th Arrondissement, is called to the scene of a ghastly and highly unusual murder, he thinks it can't have anything to do with the nine pairs of shoes and severed feet discovered outside of London's Highgate Cemetery just a few days earlier. With the help of the murdered man's gifted physician, Adamsberg delves into the victim's disturbed psyche and unexpectedly finds himself on a path that takes him deep into the haunted past of Eastern Europe, where a centuries-old horror has come to life and is claiming victims far and wide. As Adamsberg circles closer to the truth, it becomes clear that someone on the inside wants to shut down the investigation, no matter the cost.